SHOPPING ANXIETY AND “FEAR OF MISSING OUT” (FOMO) FOR PURCHASE INTENTION OF E-COMMERCE DURING PANDEMIC COVID-19 - Pristiana Widyastuti (SEAN Institute, 2022)
This study aims to measure the relationship of shopping anxiety and fear of missing out (FOMO) on the purchase intention of e-commerce. This study was conducted by distributing questionnaires to residents of Jakarta who have used e-commerce. The sampling technique used non- probability sampling with 100 respondents. The analysis data is based on Structural Equation Model (SEM) that can simultaneously perform model testing as well as structural model testing. The statistical tool is using Partial Least Square (PLS). Based on the statistical results of the research, it is concluded that during the pandemic Covid-19, the variable of shopping anxiety has no significant effect on purchasing intention of e-commerce. The respondent believes that in-store shopping behavior will return to normal supposedly post Covid. The second result concluded that the variable of FOMO has a significant effect on purchasing intention of e-commerce. Using e-commerce tends to be easy and time-saving to get the latest product updates. This FOMO habit has a significant effect on increasing purchase intention using e- commerce.